Enhancing higher order thinking skills through clinical simulation: a study on design, implementation process and outcome (IR) - Elengovan Varutharaju (2014)
The study aimed to explore, describe, and interpret the effectiveness of clinical simulation as pedagogical tool in bridging the deficiency of higher order thinking skills among Medical Assistant students and make recommendations on incorporating clinical simulation as a pedagogical tool in enhancing thinking skills and aligning the curriculum. Qualitative approach using interpretative-descriptive case study design was utilized in framing the research study. Purposive sampling using twenty (20) final year Medical Assistant students and five (5) teaching staff participated in this study. Data was collected through direct and participatory observation, interviews, and documents analysis. Thematic analysis using Stake's Countenance Model was utilized to analyze and present the findings. The study revealed a positive outlook in supporting the theme that (i) clinical simulation design facilitates the infusion of higher order thinking skills; (ii) clinical simulation that uses thinking pedagogy nurtures the development of higher order thinking skills; and (iii) clinical simulation that uses higher order thinking modality promotes learning for understanding and transfer of learning. Facilitators played a crucial role in engaging learners with higher order thinking modality and making students' thinking visible by utilizing the use of meta-cognition and self-regulation abilities, while learners became more autonomous, strategic, and motivated to apply effort and strategies in a variety of meaningful context. Clinical simulation justifies the means and the end for the development of higher order thinking skills among Medical Assistant students and warrants the incorporation across the curriculum to nurture professional knowledge and clinical competence. The findings of this study provided a thick description in assisting curriculum managers, college administrators and educators on the inclusion of clinical simulation as an instructional approach in enhancing higher order thinking skills among Medical Assistant students.